Фінансово-економічна безпека як складовасистеми управління підприємством - Ткаченко, Олександр Сергійович; Tkachenko, Oleksandr; Єрмілов, Роман Вікторович; Yermilov, Roman; Чернуха, Олексій Вікторович; Chernukha, Oleksii (Університет економіки і підприємництва, 2024)
В статті досліджено сутність фінансово-економічної безпеки як елемента системи управління підприємством. Визначено, що фінансово-економічна безпека підприємства виражає стан захищеності його фінансових і економічних інтересів від впливу внутрішніх та зовнішніх загроз. Запропоновано визначення сутності фінансово-економічна безпека як запорука його стійкості та стабільності, адже дозволяє йому можливість боротися з зовнішніми і внутрішніми загрозами, забезпечуючи безперервність діяльності та виконання своїх фінансових зобов’язань. В статті здійснено систематизацію принципів управління фінансово-економічною безпекою, котра дає можливість підприємству швидко адаптуватися до трансформації середовища зовнішнього та внутрішнього. Досліджено та згруповано фундаментальні завдання фінансовоекономічної безпеки в системі управління підприємством. The article examines the essence of fnancial and economic security as a component of the enterprise management system. Financial security is currently the most important component of economic security and the main basis of national security in a broad sense. It is also worth noting that fnancial and economic security is an important component of the enterprise management system, since it ensures the stability, effciency and competitiveness of the business. Its proper provision contributes to the achievement of strategic goals, protects against risks and ensures resistance to external and internal challenges. It is established that the fnancial and economic security of an enterprise expresses the state of protection of its fnancial and economic interests from the inﬂuence of internal and external threats. It is proposed to defne the essence of fnancial and economic security as a guarantee of its stability and stability, because it allows it to resist external and internal threats, ensuring the continuity of operations and the fulfllment of its fnancial obligations. The principles of fnancial and economic security management ensure the systematicity, effciency and stability of the management process. They defne approaches to the organization of protection of fnancial and economic interests of the enterprise, and they are also aimed at ensuring the stability of the enterprise, preventing risks and creating conditions for sustainable development. The article systematizes the principles of fnancial and economic security management, which allows the enterprise to quickly adapt to changes in the external and internal environment. The fundamental tasks of fnancial and economic security in the enterprise management system are studied and grouped. The enterprise management system is a set of methods, tools, processes and resources aimed at organizing, coordinating and controlling activities to achieve the strategic goals of the enterprise. One of the key elements of this system is fnancial and economic security, which ensures the stability and effciency of the enterprise’s functioning in a dynamic market environment. Financial and economic security is not only a component, but also the foundation of the enterprise management system
Financial and economic security as a componentof the enterprise management system
Keywords: підприємство; enterprise; безпека; security; фінансово-економічна безпека; fnancial and economic security; управління; management; загрози; threats; контроль; control; фінансовий ризик; fnancial risk